Theoretical Bases of Social and Economic Transformations in Ukraine and the World - Kovalyov Valeriy M.; Atayeva Olena A. (Problemi Ekonomiki, 2018)
The theoretical bases of the social transformations of mankind, conditioned by the modern social crisis and the emergence of the class structure of the human community in the distant past, are revealed. It is established that despite the existing economic concept of the human “bio — socio — spiritual” essence, as a matter of fact, it is determined by a triune material, spiritual, and social nature, according to the requirements of which, historically justified social changes in the human community take place. It is asserted that the emergence and development of the new social science “human studies”, which connects human knowledge and scientific achievements in all spheres of human activity, will play a decisive role in the system of natural social changes of mankind. The basic principles of the formation and organization of this science and their manifestations are determined. There revealed the economic essence of the notion “sociality”, its place and role in transformation processes as a category not attributed to the human nature of an individual but to society as a whole, with the disappearance of the class nature of which prerequisites for transforming it into a spiritually humanistic dominant of the entire society will arise. Materiality is defined as the primary quality of the world and man, as a manifestation of his physical state, which is supported by the consumption of material resources. It is recognized that the sources of social transformations of mankind in the future are realized through such prerequisites as: the system of objectively operating laws of development of nature and society (the laws of equilibrium, correspondence of production relations to the level of productive forces, human evolution; the basic economic law; laws regulating labor payment); the system of scientific knowledge; objectively operating conditions concerning the possibility of such transformations that are stimulated by global changes in the level and quality of productive forces as a result of the application of new nanotechnologies, robotization, artificial intelligence, holographic measurement of the universe, new types of energy, etc.